Translation Peculiarities of Polysemantic Words (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2025)
This paper delves into the multifaceted challenges inherent in translating polysemy, a linguistic phenomenon where a single word carries multiple meanings, from English. It underscores the significance of polysemy in enriching language but also highlights the complexities it presents for translators striving for accurate and nuanced renderings. The analysis emphasizes the importance of contextual awareness and cultural sensitivity in navigating the ambiguities that arise when a word’s intended meaning is not immediately clear. By examining how translators grapple with polysemic words, particularly in complex literary texts, the study reveals the strategies employed to maintain semantic fidelity while ensuring naturalness and coherence in the target language. Examples drawn from Shakespeare’s “Hamlet” are provided to illustrate the specific hurdles encountered when translating idiomatic expressions, figurative language, and specialized terminology that rely heavily on polysemic interpretation. Ultimately, the paper argues that a successful translation of polysemy demands a deep understanding of both the linguistic and cultural landscapes of the source and target languages, as well as a keen awareness of the potential for misinterpretation and the need for creative solutions to preserve the richness and depth of the original text.